2023
DOI: 10.1097/prs.0000000000010798
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of the Velopharynx: Clinical Findings in Patients with Velopharyngeal Insufficiency

Abstract: Background: Magnetic resonance imaging (MRI) is the only imaging modality capable of directly visualizing the levator veli palatini (LVP) muscles: the primary muscles responsible for velopharyngeal closure during speech. MRI has been used to describe normal anatomy and physiology of the velopharynx in research studies, but there is limited experience with use of MRI in the clinical evaluation of patients with velopharyngeal insufficiency (VPI). Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…This is particularly relevant, given that recent studies have noted that small quantitative differences (<1 mm) have been reported to influence velopharyngeal function, and these differences may be correlated with the perception of hypernasality. 56,57 For example, in patients that demonstrate velopharyngeal insufficiency, use of the curvilinear measurement provides more accurate quantitative assessment of the velar morphology and likelihood for postoperative VP function, particularly as it relates to distraction osteogenesis 30 and obstructive sleep apnea. 58 Furthermore, functional differences may also be observed when assessing velar length during phonation due to patient-specific anatomy postpalatoplasty, again highlighting the need to precisely measure this structure using a curvilinear measurement.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly relevant, given that recent studies have noted that small quantitative differences (<1 mm) have been reported to influence velopharyngeal function, and these differences may be correlated with the perception of hypernasality. 56,57 For example, in patients that demonstrate velopharyngeal insufficiency, use of the curvilinear measurement provides more accurate quantitative assessment of the velar morphology and likelihood for postoperative VP function, particularly as it relates to distraction osteogenesis 30 and obstructive sleep apnea. 58 Furthermore, functional differences may also be observed when assessing velar length during phonation due to patient-specific anatomy postpalatoplasty, again highlighting the need to precisely measure this structure using a curvilinear measurement.…”
Section: Discussionmentioning
confidence: 99%
“…19 As a result, most patients scheduled for velopharyngeal MR imaging will typically be between these ages; however, velopharyngeal MR imaging has been demonstrated in VPI surgical planning for patients ranging in age from 3 to 39 years (n ¼ 113 patients) at a single cleft craniofacial center in the United States. 10 Patients are required to be imaged both at rest and while producing and sustaining specific sounds. While typical MR imaging in young children is often performed with sedation or general anesthesia with use of a laryngeal mask airway to support the airway for breathing, successful velopharyngeal MR imaging requires that the patient be fully awake using a nonsedated protocol with no contrast or laryngeal mask airway.…”
Section: Velopharyngeal Mr Imaging Protocolmentioning
confidence: 99%
“…7,8 MR imaging is a relatively newer clinical imaging diagnostic tool in cleft care that is being introduced into cleft craniofacial care units, particularly in the United States. [9][10][11] The interest in velopharyngeal MR imaging is primarily due to the advantage of MR imaging in visualizing the velopharyngeal musculature, which is not possible using nasopharyngoscopy and videofluoroscopy. [9][10][11] Similar to videofluoroscopy, MR imaging can be used to accurately quantify key velopharyngeal structures with the added benefits of section specificity (eg, the ability to select a precise midsagittal section without head rotation) and lack of ionizing radiation, which is present, though minimal, in videofluoroscopy.…”
mentioning
confidence: 99%
See 1 more Smart Citation